The Effect of Profitability, Investment Policy, and Financial Performance on Stock Returns in Infrastructure Sector Companies on the IDX - Anggreani, Yulistina; Suhardi, Suhardi; Afrizal, Afrizal; Andriana, Nana (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
The purpose of this study is to examine the impact of profitability, investment strategy, and financial results on stock returns of companies in the infrastructure sector listed on the Indonesia Stock Exchange (IDX) for the period 2020-2024. The methodology used consists of panel data regression using a quantitative framework, referring to secondary data sourced from companies' annual financial reports. The independent variables investigated include Return on Assets (ROA) as a profitability metric, total assets that serve as a proxy for investment strategy, and current ratio as a benchmark for financial performance. The research findings show that ROA and total assets exert a positive and statistically significant influence on stock returns, while the current ratio shows no significant impact. These findings indicate that investors tend to consider profitability and asset strength when making investment decisions in the infrastructure sector. This study provides practical implications for company management and investors, and recommends further research by including external variables and comparing with other sectors to obtain a more comprehensive understanding.